Nontraumatic instability of the middle finger extensor digitorum communis tendon in a child. A case report - Michał Zakryś; Michał Górecki; Piotr Czarnecki (Chirurgia Narządów Ruchu i Ortopedia Polska)
The instability of extensor tendons in the hand is mostly an outcome of rheumatoid arthritis, but can also be a manifestation of sagittal band rupture as a result of injury, often during boxing. A 14-year-old patient was admitted to a hand surgery department due to the painful instability of the middle finger extensor digitorum communis in the right hand. No trauma was reported, and the symptoms appeared about a year earlier with a gradual aggravation. Prior to admission, the patient underwent an unsatisfactory attempt at conservative treatment with an extension splint. A surgical centralisation and stabilisation of the middle finger extensor digitorum communis was implemented according to the Wheeldon technique. The treatment comprised resection anovergrown joint capsule, stabilising the tendon with a flap created from neighbouring juncturae tendinum and subsequent rehabilitation. The procedure resulted in an excellent functional outcome. With a one-year-long follow-up, a return to normal function and sport was achieved, and the patient reports no abnormalities or complaints.